Efektivitas Cognitive Behavior Therapy dan Psikoedukasi Keluarga dalam Menurunkan Perilaku Menentang pada Remaja dengan Riwayat Trauma Pengasuhan: Studi Kasus - Nazarlin Nazarlin; Sri Novia Martin; Melati Putri Ulandari; Rizkia Maghfirah; Aflah Zakinov Irta (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aimed to examine the effectiveness of Cognitive Behavioral Therapy (CBT) and family psychoeducation in reducing oppositional behavior among adolescents with a history of developmental relational trauma. The participant was a 17-year-old male adolescent who exhibited symptoms of irritability, emotional sensitivity, social withdrawal, interpersonal conflicts in a residential care setting, and difficulties in emotion regulation. Data were collected through clinical interviews, behavioral observations, graphic psychological tests, the Sack's Sentence Completion Test (SSCT), and intervention outcome evaluations. The assessment revealed maladaptive cognitive schemas characterized by dysfunctional core beliefs such as